2012
DOI: 10.1017/s1751731112001164
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of several factors of variation of gestation loss in breeding mares

Abstract: The files for ultrasound diagnosis of gestating mares belonging to the French equine herd recorded for 3 consecutive years were joined with the files for foal birth of these same mares, allowing the statistical analysis of factors of pregnancy loss. For 28 872 positive diagnoses of gestation, 2898 losses were recorded, that is, a global rate of gestation interruption of 9.12%. The etiology of these interruptions is mainly extrinsic: the year and month of insemination, as well as region for climatic reasons. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Squires et al (2013) also reported significantly lower dystocia (8.5%) for maiden mares compared with multiparous mares (14.2% for foaling mares and 12.7% for barren mares), again in thoroughbreds. Our results were comparable to those reported by Langlois et al (2012) when they analysed gestation losses (i.e. between diagnosis of gestation and birth).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Squires et al (2013) also reported significantly lower dystocia (8.5%) for maiden mares compared with multiparous mares (14.2% for foaling mares and 12.7% for barren mares), again in thoroughbreds. Our results were comparable to those reported by Langlois et al (2012) when they analysed gestation losses (i.e. between diagnosis of gestation and birth).…”
Section: Discussionsupporting
confidence: 91%
“…No differences in the incidence of dystocia depending on the month of parturition were reported by Squires et al. (2013) and an increase of gestation losses was observed by Langlois et al (2012) for mares that were bred during month of last mating. In dairy cattle, on the contrary, winter months are the less favourable (Steinbock et al , 2003; Eaglen and Bijma, 2009).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Researchers are addressing equine heredity with cohorts of a previously unseen scale. In France, where all breed registry data includes ultrasound confirmation of pregnancy under the Haras Nationaux (national studbook) regulations, researchers retrospectively studied over 350,000 gestations, with the aim of refining knowledge of the sire and dam’s genetic contribution to gestation length and fetal health . Such studies enable GL data to be collected on an equally major scale.…”
Section: Overviewmentioning
confidence: 99%